Comparative Analysis between the United States and Indonesia Regarding Product Liability of Food and Beverage Tenants within the Tourism Industry - Utomo, Shadrina R. T.; Marlyna, Henny; Anggraini, Ayu Galuh (Technology and Economics Law Journal, 2025)
This research analyzes on how the laws in Indonesia and Florida, United States (U.S.) regulate the product liability of tourism entrepreneurs, whether as the food and beverage tenant within the tourism area or as the tourism operator, who have caused tourists to suffer from food poisoning. The Law Number 10 Year 2009 concerning Tourism the obligation for tourism entrepreneurs in providing insurance is only for high-risk tourism businesses. Tourism entrepreneurs in Indonesia have made various safety measures by fulfilling the sanitation and hygiene requirements, and preparing medical protocols. Meanwhile in Florida, tourism entrepreneurs have added accessibility efforts for tourists with special dietary needs, such as food allergies. The product liability in Law Number 9 Year 1999 contains the reversed burden of proof element. Meanwhile, the product liability in the 2024 Florida Statutes has two theories which are the strict liability or negligence. This article concludes that there needs to be a specific regulation for food and beverage tenants within the tourism area in providing compensation for tourists who suffered from food poisoning, and an apportionment of damages for every party liable for the injury.